Correlation of crystalline structure and dynamic mechanical characteristics of nanocomposites: epoxy polymer–CdO–polyaniline - Bardadym, Y.V.; Vilensky , V.O.; Gomza, Y.P.; Kercha, Yu.Yu.; Tkalich, M.G.; Zagorny, M.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The first stage of the X-ray diffraction analysis of nanocomposites EP – 3%CdO and EP – 3% (CdO + PAn) is carried out. It is established that CdO does not change its crystal cubic system. Forming the chemical network of Thermoses causes decreasing the longitudinal size of crystals CdO from 24.9 down to 14.2 nm. The dynamic mechanical study of nanocomposites has shown that their forming under the action of CMF or CEF leads to a depression of the elasticity modulus in comparison with specimens, which were formed under ordinary conditions. Evaluating the dependence of the energy of activation at the glass transition of EP on the cured conditions shows that the action of physical fields allows one to directedly change this characteristic of the polymer matrix.